Phototransistor with nanocrystalline Si/amorphous Si bilayer channel - Vygranenko, Yuri (2011)
We report a field-effect phototransistor with a channel comprising a thin nanocrystalline silicon transport layer and a thicker hydrogenated amorphous silicon absorption layer. The semiconductor and dielectric layers were deposited by radio-frequency plasma enhanced chemical vapor deposition. The phototransistor with channel length of 24 microns and photosensitive area of 1.4 mm(2) shows an off-current of about 1 pA, and high photoconductive gain in the subthreshold region. Measurements of the quantum efficiency at different incident light intensities and biasing conditions, along with spectral-response characteristics, and threshold voltage stability characterization demonstrate the feasibility of the phototransistor for low light level detection.